"Perplex'd in extreme" or (in)fidelity in translation : Reading and performing Shakespeare in contemporary Argentina - Montezanti, Miguel Ángel (2005)
The purpose of this article is to illustrate the reception of some Shakespearean plays in Argentina. Part 1 focuses on the limitations imposed by the audience's moral taste upon the translator's choices. Part 2 analyzes two cases in which source language (SL) texts have been heavily transformed, i.e., "appropriated" by two Argentine contemporary playwrights.